Physical–Mathematical Modeling and Simulations for a Feasible Oscillating Water Column Plant - Fabio Caldarola; Manuela Carini; Alessandro Costarella; Gioia De Raffele; Mario Maiolo (Mathematics, 2025)
The focus of this paper is placed on Oscillating Water Column (OWC) systems. The primary aim is to analyze, through both mathematical modeling and numerical simulations, a single module (chamber) of an OWC plant which, in addition to energy production, offers the dual advantage of large-scale integration into port infrastructures or coastal defense structures such as breakwaters, etc. The core challenge lies in optimizing the geometry of the OWC chamber and its associated ducts. A trapezoidal cross-section is adopted, with various front wall inclinations ranging from <semantics>90°</semantics> to <semantics>45°</semantics>. This geometric parameter significantly affects both the internal compression ratio and the hydrodynamic behavior of incoming and outgoing waves. Certain inclinations revealed increased turbulence and notable interference with waves reflected from the chamber bottom which determined an unexpected drop in efficiency. The optimal performance occurred at an inclination of approximately <semantics>55°</semantics>, yielding an efficiency of around 12.8%, because it represents the most advantageous and balanced compromise between counter-trend phenomena. A detailed analysis is carried out on several key parameters for the different configurations (e.g., internal and external wave elevations, crest phase shifts, pressures, hydraulic loads, efficiency, etc.) to reach the most in-depth analysis possible of the complex phenomena that come into play. Lastly, the study also discusses the additional structural and functional benefits of inclined walls over traditional parallelepiped-shaped chambers, both from a structural and construction point of view, and for the possible use for coastal defense.